2018
DOI: 10.5194/acp-18-3485-2018
|View full text |Cite
|
Sign up to set email alerts
|

Temporally delineated sources of major chemical species in high Arctic snow

Abstract: Abstract. Long-range transport of aerosol from lower latitudes to the high Arctic may be a significant contributor to climate forcing in the Arctic. To identify the sources of key contaminants entering the Canadian High Arctic an intensive campaign of snow sampling was completed at Alert, Nunavut, from September 2014 to June 2015. Fresh snow samples collected every few days were analyzed for black carbon, major ions, and metals, and this rich data set provided an opportunity for a temporally refined source app… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 81 publications
3
17
0
Order By: Relevance
“…Observed and simulated seasonal cycles of BC and sulfate typically show a maximum in near-surface concentrations in March or April (Barrie and Hoff, 1985;Eckhardt et al, 2015;Garrett et al, 2010;Sharma et al, 2006) and clean conditions in the summertime. Natural emissions of BC from vegetation fires are considerable in late spring to early summer in the Arctic and at mid-latitudes (Mahmood et al, 2016). Production of sulfate aerosol is more efficient in the warm than the cold seasons (Mahmood et al, 2018;Tesdal et al, 2015).…”
Section: Background On Arctic Aerosolmentioning
confidence: 99%
See 2 more Smart Citations
“…Observed and simulated seasonal cycles of BC and sulfate typically show a maximum in near-surface concentrations in March or April (Barrie and Hoff, 1985;Eckhardt et al, 2015;Garrett et al, 2010;Sharma et al, 2006) and clean conditions in the summertime. Natural emissions of BC from vegetation fires are considerable in late spring to early summer in the Arctic and at mid-latitudes (Mahmood et al, 2016). Production of sulfate aerosol is more efficient in the warm than the cold seasons (Mahmood et al, 2018;Tesdal et al, 2015).…”
Section: Background On Arctic Aerosolmentioning
confidence: 99%
“…An analysis of results from simulations with four different models in NETCARE (Mahmood et al, 2016) indicates that the main source of BC in the Arctic is long-range transport from mid-latitudes. The long-range transport of BC to the Arctic is particularly efficient in midwinter and then decreases in efficiency, reaching a minimum in March and April.…”
Section: Springtime Aerosol: Sources and Vertical Distributionmentioning
confidence: 99%
See 1 more Smart Citation
“…To take advantage of the high temporal resolution of the samples, the data were also used to assess potential sources 10 contributing to chemical species in snow using a combination of positive matrix factorization and FLEXPART potential emission sensitivity analysis (Macdonald et al, 2018). The best positive matrix factorization solution consisted of seven source factors (sea salt, crustal metals, BC, carboxylic acids, nitrate, non-crustal metals, and sulfate), reflecting a balance between natural and anthropogenic sources.…”
Section: Aerosol Deposition To Snowmentioning
confidence: 99%
“…Previously, rBC preserved in ice cores [6,[11][12][13], modern lake sediments [14,15], and snow samples [16][17][18][19] has been used as a proxy of regional biomass burning and fossil fuel combustion during the past century. These studies demonstrated synchronous variations in rBC emissions with past climate [11,12] and anthropogenic activities associated with industrialization and biomass burning [6,7,15].…”
Section: Introductionmentioning
confidence: 99%